2020
DOI: 10.1002/jlb.5ab0320-415rrrrr
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing TNFR2 antagonism for immunotherapy with tumor microenvironment specificity

Abstract: Most approved cancer immunotherapies lack T‐regulatory (Treg) or tumor specificity. TNF receptor 2 (TNFR2) antibody antagonism is emerging as an attractive immunotherapy due to its tumor microenvironment (TME) specificity. Here we show that the human TNFR2 receptor is overexpressed on both human tumor cells and on human tumor‐residing Tregs, but negligibly expressed on beneficial T effectors (Teffs). Further, we found widespread, if variable, TNFR2 expression on 788 human tumor cell lines from diverse cancer t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 30 publications
1
26
0
Order By: Relevance
“…molecular arrangement leading to super-agonism. It should also be noted that although in our experience the hIgG2 isotype has evoked agonism for CD40 and other TNFRs, there are examples where the heavy chain of an anti-TNFR2 mouse IgG2b has been replaced with that of hIgG2 to provide a more powerful antagonist 54 . It remains unclear if the Fc domain of these chimeric antibodies are required for their antagonistic function but indicates that the underpinning clustering geometry is important in each case.…”
Section: Discussionmentioning
confidence: 91%
“…molecular arrangement leading to super-agonism. It should also be noted that although in our experience the hIgG2 isotype has evoked agonism for CD40 and other TNFRs, there are examples where the heavy chain of an anti-TNFR2 mouse IgG2b has been replaced with that of hIgG2 to provide a more powerful antagonist 54 . It remains unclear if the Fc domain of these chimeric antibodies are required for their antagonistic function but indicates that the underpinning clustering geometry is important in each case.…”
Section: Discussionmentioning
confidence: 91%
“…25,80 Therefore, we (Xin Chen and Joost J. Oppenheim) and Dr. Faustman proposed that TNFR2 may be harnessed as a druggable target to enhance anti-tumor immune responses. 28,61,82,[84][85][86][87][88][89] This idea is supported by a number of studies, as summarized in Table 2.…”
Section: Tnfr2-expressing Tregs: a Major Cellular Mechanism In Tumor Immune Evasionmentioning
confidence: 74%
“…82 A recent study of 788 commercially available human cancer cell lines from diverse cancer tissues indicates that various levels of TNFR2 are expressed, while hematopoietic and lymphoid cell lines express the highest levels of TNFR2. 86 An immunohistochemistry (IHC) study of 431 tissue specimens from esophageal squamous cell carcinoma (ESCC) patients found that TNFR2 expression is higher in • Concurrent or a prior dose of TY101 with anti-PD-1 showed maximum benefits.…”
Section: Expression Of Tnfr2 On Tumor Cellsmentioning
confidence: 99%
See 2 more Smart Citations